2012
DOI: 10.1097/brs.0b013e318254155a
|View full text |Cite
|
Sign up to set email alerts
|

Pullout Analysis of a Lumbar Plate With Varying Screw Orientations

Abstract: Significant difference was found between certain screw-angle configurations; however, when compared with simply placing the screws straight in, the difference was never more than 8%. This implies that there is greater freedom in the angle and placement of screws than previously thought. Our results show that there is little change in fixation strength when placing the screw in a different direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been described in the previous studies that the strain occurred mainly around the screws, and the main reasons were the pressure of the thread on the bone in contact with it destroyed the bone around the screw and the stiffness of the vertebrae was weaker than that of the screw 14 , 17 , 35 ; the results of current study were coincided with these findings (Supplemental Digital Content Figure 8, http://links.lww.com/BRS/B980 ). At the same time, the strain on the vertebrae was mainly in the vicinity of the screw ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in the previous studies that the strain occurred mainly around the screws, and the main reasons were the pressure of the thread on the bone in contact with it destroyed the bone around the screw and the stiffness of the vertebrae was weaker than that of the screw 14 , 17 , 35 ; the results of current study were coincided with these findings (Supplemental Digital Content Figure 8, http://links.lww.com/BRS/B980 ). At the same time, the strain on the vertebrae was mainly in the vicinity of the screw ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Polyurethane blocks are a well‐established bone surrogate and are recommended for interbody fusion device testing. However, they do not include a vertebral cortical shell and endplate, which represents a potential limitation for the clinical extrapolation of results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pullout strength of an ALP system that includes four individual screws was complicated. Rios et al [10] evaluated the pullout force of the anterior lumbar interbody fixa tion plate using experimental and finite element analyses. They concluded that the parallel constructs revealed the maximum pullout force in both the foam model and the bovine cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with spinal decompression treatment using the ALP system still face compli cations such as implant loosening and breakage [7][8][9]. Past studies suggested that locking screws should be inserted with a particular inclined angle to strengthen the biomechanical performances of ALP systems [10], but oppo site conclusion has also been reached [9], Unfortunately, the screw orientations determined in past studies are mainly based on the surgeon's experience without biomechanical evidence. Past studies suggested that locking screws should be inserted with a particular inclined angle to strengthen the biomechanical performances of ALP systems [10], but oppo site conclusion has also been reached [9], Unfortunately, the screw orientations determined in past studies are mainly based on the surgeon's experience without biomechanical evidence.…”
Section: Introductionmentioning
confidence: 99%